Home Surgical Skill Training Resources for Obstetrics and Gynecology Trainees During a Pandemic. Issue 1 (July 2020) - Hoopes, Sarah; Pham, Truce; Lindo, Fiona M.; Antosh, Danielle D.
Abstract : The coronavirus disease 2019 (COVID-19) pandemic has created a unique educational circumstance in which medical students, residents, and fellows find themselves with a gap in their surgical training. We reviewed the literature, and nine categories of resources were identified that may benefit trainees in preventing skill decay: laparoscopic box trainers, virtual reality trainers, homemade simulation models, video games, online surgical simulations, webinars, surgical videos, smartphone applications, and hobbies including mental imagery. We report data regarding effectiveness, limitations, skills incorporated, cost, accessibility, and feasibility. Although the cost and accessibility of these resources vary, they all may be considered in the design of remote surgical training curricula during this unprecedented time of the COVID-19 pandemic. Abstract : Resources are available for remote laparoscopic and basic surgical training, including core skills, psychomotor, visual–spatial, and cognitive, to improve gaps in surgical training during the coronavirus disease 2019 (COVID-19) pandemic.